H. pylori-negative peptic ulcer: state-of-the-art - M. A. Osadchuk; A. M. Osadchuk; A. A. Sibrjaev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern data on epidemiology, etiology, pathogenesis, clinical presentation, diagnostics, differential diagnostics and treatment of H. pylori-negative peptic ulcer.Key points. Increase in number of cases of such disorders detection is demonstrated. Basic concept on etiology and pathogenesis of H. pylori-negative peptic ulcer is presented. Its association with more severe course of disease, higher morbidity and mortality rates is emphasized. Approaches to diagnostics, differential diagnostics and treatment are revealed.Conclusion. The review presents epidemiology, etiology, pathogenesis, clinical features of H. pylorinegative peptic ulcer. Existing problems in this area and possible ways out are described in detail.